Composite model-based estimate of the ocean carbon sink from 1959 to 2022 - J. Terhaar; J. Terhaar (Biogeosciences)
The ocean takes up around one-quarter of anthropogenically emitted carbon and is projected to remain the main carbon sink once global temperatures stabilize. Despite the importance of this natural carbon sink, estimates of its strength over the last decades remain uncertain, mainly due to too few and unevenly sampled observations and shortcomings in ocean models and their setups. Here, I present a composite model-based estimate of the annually averaged ocean carbon sink from 1959 to 2022 by combining the higher-frequency variability of the annually averaged estimates of the carbon sink from ocean models in hindcast mode and the long-term trends from fully coupled Earth system models. Ocean models in hindcast mode reproduce the observed climate variability, but their spin-up strategy likely leads to long-term trends that are too weak, whereas fully coupled Earth system models simulate their own internal climate variability but better represent long-term trends. By combining these two modelling approaches, I keep the strength of each approach and remove the respective weaknesses. This composite model-based estimate of the ocean carbon sink from 1959 to 2022 is 125±8 Pg C and is similar in magnitude to the best estimate of the Global Carbon Budget but 70 % less uncertain.